How BAE systems turned a scandal into a success - Ashman, Ian (Henry Stewart Talks, 2016)
This case study describes the process undertaken by BAE to develop and implement an ethical code of conduct, following a scandal surrounding the sale of products to Saudi Arabia in 1985, and investigated in 2005.